Complicated cutaneous leishmaniasis caused by an imported case of Leishmania tropica in Japan: a case report - Hiroyuki Kitano; Chizu Sanjoba; Yasuyuki Goto; Kazumasa Iwamoto; Hiroki Kitagawa; Toshihito Nomura; Keitaro Omori; Norifumi Shigemoto; Michihiro Hide; Yoshitsugu Matsumoto; Hiroki Ohge (Tropical Medicine and Health, 2021)
Abstract Background Leishmaniasis is not endemic in Japan, and imported cases are rare. However, there are increasing concerns regarding imported cases of cutaneous leishmaniasis from endemic countries to Japan. This report describes a case of imported cutaneous leishmaniasis that was diagnosed and treated in Japan. Case presentation A 53-year-old Pakistani man presented with skin lesions on both malleoli of his right ankle and the dorsum of the left foot. The skin lesions manifested as erythematous nodules surrounding an ulcer in the center of the lesion. The lesions of the malleoli of his right ankle each measured 3 × 3 cm, and the lesion on the top of his left foot measured 5 × 4 cm. He had been living and working in Japan but had a history of a visit to Pakistan for about 2 months in 2018. The skin lesions were biopsied. Giemsa and hematoxylin and eosin staining of biopsy samples showed amastigotes of Leishmania in macrophages, and the presence of Leishmania was confirmed by skin tissue culture. Polymerase chain reaction using biopsy specimens identified Leishmania parasites, and DNA sequence analysis revealed that the species was Leishmania tropica. The patient was treated with intravenous liposomal amphotericin B for 6 days. The erythema disappeared, and the erythematous nodules resolved within 3 weeks. Conclusion This is the first report of imported cutaneous leishmaniasis caused by L. tropica from Pakistan, and it is interesting that all three testing modalities showed positive results in this case.